Implementation of STEM (Science Technology Engineering and Mathematics) Learning Model Based on Local Wisdom on Student Learning Outcomes - Dewi, Ardiana Fatma; Wakhidah, Fina Alya Nur; Sari, Dwi Ratna; Arifinta, Hasna Nisa; Ni’amahah, Naila Lutfiatun; Ilmia, Siti Mazro’atul; Sholihah, Tri Eva (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2024)
The rapid development of science and technology has given rise to various innovations in the field of technology that are created to facilitate activities, especially in the field of education. Creative thinking and critical thinking skills are very much needed following the demands of 21st-century skills, namely so that students have various abilities, including critical thinking, creative thinking, communication and collaboration. STEM is an integrative learning approach that combines Knowledge (Science), Technology (Technology), Engineering (Engineering), and Mathematics (Mathematics). Several studies have shown that the STEM approach positively affects student learning, so this study tries to implement STEM based on local wisdom on learning outcomes. This study aims to determine how student learning outcomes are before and after providing a STEM learning model based on local wisdom. The type of research used is quantitative with an experimental method. Sample selection uses a simple random sampling technique, with research subjects being grade IX students of SMP Muhammadiyah Kediri. The results of the study showed that the average student learning outcomes before the action were relatively low; after being given treatment, the average student learning outcomes increased. The results obtained using the paired t-test were that the significance value of learning outcomes was 0.000 <0.05, meaning that there was a difference in the average learning outcomes of students before and after the local wisdom-based STEM learning model provision.